2009
DOI: 10.1080/10242690902868301
|View full text |Cite
|
Sign up to set email alerts
|

Military Spending and Economic Growth in Sri Lanka: A Time Series Analysis

Abstract: In this paper, we employ a VAR analysis to examine the nexus between military spending and economic growth in Sri Lanka which, due to the civil war there, has witnessed a significant increase in military spending over the last three decades while also recording healthy economic growth. The study finds that, compared with non-military spending, military spending exerts only a minimal positive impact on real GDP. Over a 10-year period, a 1% increase in non-military spending increases GDP by 1.6%. In contrast, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
4
18
1
2
Order By: Relevance
“…It is documented that a 1% increase in real interest rate is linked with 0.0418% decline in economic growth. These findings are consistent with the empirical results of Atesoglu (2002), Halicioglu (2004) and Wijeweera and Webb (2009).…”
Section: Empirical Estimationsupporting
confidence: 83%
See 3 more Smart Citations
“…It is documented that a 1% increase in real interest rate is linked with 0.0418% decline in economic growth. These findings are consistent with the empirical results of Atesoglu (2002), Halicioglu (2004) and Wijeweera and Webb (2009).…”
Section: Empirical Estimationsupporting
confidence: 83%
“…These findings are consistent with the existing literature such as Khilji and Mahmood (1997), Atesoglu (2002), Karagol and Palaz (2004), Smith and Tuttle (2008), Tang (2008) and Keller et al (2009). The estimated coefficient of government non-military spending is showing positive impact on economic growth supporting the views of Halicioglu (2004), Yildirim et al (2005) and Wijeweera and Webb (2009). The inverse relationship is also witnessed between real interest rate and economic growth, and is consistent with findings of Halicioglu (2004).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
See 2 more Smart Citations
“…A series of studies found that military spending neglected/reducing the economic growth [Smith, (1977) ;Boretsky, (1975) ;Sivard, (1977); Atesoglu (2002), Ocal and Brauer (2007) and Smith and Tuttle (2008)]. However, the opposite evidence also exists in the earlier literature that military spending promotes economic growth [Benoit (1973[Benoit ( , 1978; Halicioglu (2003Halicioglu ( , 2004; Wijeweera and Webb (2009) ;Atesoglu, (2009) and, Wijewerra and Webb (2011)]. …”
Section: Introductionmentioning
confidence: 69%